The irregular populist: André Ventura: the lider of Chega - Pimenta, David (2022)
This paper aims to measure, for the first time, the level of populist rhetoric of André Ventura – the leader of the Chega party. We did so by analyzing a total of sixteen discursive elements (selected speeches, interviews and tweets, between 2020 and 2022), using the holistic grading method with two graders. Despite a total average of 1.14 (on a scale ranging from 0 to 2), which would suggest mild populism, we managed to identify several features of manifest populist rhetoric, such as a dualistic framework of politics, an agonistic dichotomy between Chega and the political and economic establishment – the “system” –, and an attempt to rekindle political conflict seen as a moral battle where Chega would act as the sole instrument to save Portugal from its enemies and problems. Taking this into consideration, the main conclusion of this paper is the classification of André Ventura as an irregular populist, considering the constant fluctuation of his populist rhetoric in order to adapt to the place, the audience, and, most likely, the political moment and the intended consequences of the speech itself